Effect of Aloe vera extract on the improvement of the respiratory activity of leukocytes of matrinxã during the transport stress - Zanuzzo, Fábio Sabbadin [UNESP]; Biller-Takahashi, Jaqueline Dalbello [UNESP]; Urbinati, Elisabeth Criscuolo [UNESP] (Sociedade Brasileira de Zootecnia, 2012)
This study evaluated the effect of extract of Aloe vera in the transport water of matrinxã (Brycon amazonicus) fish on stress response and leukocyte respiratory activity. Fish was transported for 4 h in water containing Aloe at levels 0; 0.02; 0.2 and 2 mg/L, and sampled before transport 2, 4, 24 and 96 h after for determination of plasma glucose and respiratory activity of leukocytes. An additional in vitro assay was conducted with another fish species, pacu (Piaractus mesopotamicus), to test the respiratory burst of leukocytes exposed to Aloe extract (0.0, phosphate-buffered saline (PBS) only) at 0.1, 0.2, 0.5 and 1 mg/L). Plasma glucose increased after 2 and 4 h of transport and returned to control levels within 24 h, but the addition of Aloe in the transport water did not affect the level of blood glucose. However, at 2 h of transport, Aloe enhanced the respiratory activity of leukocytes in a dose-dependent way. The highest value of respiratory burst activity of leukocytes was observed in the fish transported in water containing Aloe at 2 mg/L. The enhancing effect of the plant extract on the production of oxygen radicals was confirmed in vitro in leukocytes of pacu incubated in Aloe at concentrations 0.1 and 0.2 mg/L. The results suggest that Aloe vera is a modulator of the immune system in fish improving the innate immune response tested.
Keywords: Brycon amazonicus; innate immune system; oxidative burst; white blood cells